Playing Promotional Politics: Mythologizing Hockey and Manufacturing “Ordinary” Canadians - Scherer, Jay; McDermott, Lisa (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2011)
Over 15 years ago, Andrew Wernick described a new stage of promotion within the mainstream politics of advanced capitalist democracies through which political dialogue was effectively subsumed by the language and practices of contemporary marketing and image-making spectacles. In this article, we examine how the national sport of hockey and its associated traditions and cultural identities continue to be mythologized and deployed in the new millennium for the purpose of contemporary political promotional strategies. We argue that, as a central element of national popular culture, hockey remains the pre-eminent signifier of a particular ‘brand’ of Canadianness for the current federal Conservative Government as it massages its neoliberal political platform to a demographic of imagined, “ordinary Canadians”—a key concept of neoliberal discourse that is redefining citizenship and identity across contemporary Canada.